Multi-Hazard Fragility Analysis of Offshore Wind Turbine Portfolios using Surrogate Models. (September 2022) - Seo, Junwon; Pokhrel, Jharna; Hu, Jong Wan
Abstract: This paper deals with a surrogate modeling-based fragility estimate of monopile offshore wind turbine (OWT) towers subjected to wind and wave loadings. The monopile 5-MW OWT specified by the National Renewable Energy Laboratory (NREL), United States was used as the base model for this study. Aero- and hydrodynamic simulations of the OWT were first performed via Fatigue, Aerodynamics, Structures, and Turbulence (FAST) developed by the NREL to determine its critical wave-and-wind responses, to determine peak tower top deflections, flexural moments, and shear forces. Through least squares regression with the simulation data, two surrogate models, Response Surface Metamodel (RSM) and Stepwise Multiple Linear Regression (SMLR) were developed to predict the critical OWT responses caused by both wind and wave loads and to develop its fragility curves at a low computational cost. Responses and fragility curves resulting from each of the surrogate models were compared to those from the FAST simulation, demonstrating the effectiveness of the RSM in terms of accuracy to replicate the FAST results. As a result of the comparison, the RSM was adopted as the final model to estimate the multi-wind-and-wave vulnerability of the OWT in terms of fragility surfaces considering uncertainties in a broad spectrum of its loads and capacities. Major findings indicated that the wind speed was observed to be the most critical load parameter for peak tower top deflections with response observed in the range of 2.2 5 m at a wind speed of 5 m/s to 5.5 m at 70 m/s, while the wave height appeared to be the major contributor to the vulnerability on flexural moments with the observed peak value of 1.75 × 10 8 Nm at a wave height of 1 m increased to 5.75 × 10 8 Nm at 20 m. It was also found that structural characteristics parameters related to the OWT's capacities, including hub height, rotor diameter, and monopile thickness have a significant impact on the overall vulnerability with one-quarter exceeding probability for mudline flexure was noted at 83.26 m, 151 m, and 0.133 m, respectively. Highlights: Surrogate models were created to estimate multi-hazard responses of offshore wind turbines. Aero- and hydrodynamic simulations of the wind turbines were performed using FAST. Peak tower top deflections, flexural moments, and share forces were determined. Multi-hazard fragility analyses were conducted using the surrogate models.